2012
DOI: 10.1177/0269215511435424
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rehabilitation of Memory in Neurological Disabilities (ReMiND): a randomized controlled trial

Abstract: Objective: The evidence for the effectiveness of memory rehabilitation is inconclusive. The aim was to compare the effectiveness of two group memory rehabilitation programmes with a self -help group control. Design: Single-blind randomized controlled trial. Participants: Participants with memory problems following traumatic brain injury, stroke or multiple sclerosis were recruited from community settings. Interventions: Participants were randomly allocated, in cohorts of four, to compensation or restitution gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 25 publications
(26 reference statements)
1
74
0
Order By: Relevance
“…If sessions were missed, for example due to illness, then participants were invited to attend the next session early in order to catch up on the missed material. The programme was based on the group programmes previously evaluated, 6,20 but both restitution and compensation strategies were included for all participants. The programme included: one introductory session; three sessions on attention training; three sessions on internal memory strategies; two sessions on external memory aids; and one concluding session to bring together everything that had been learned and to reflect on the best strategies for each individual.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If sessions were missed, for example due to illness, then participants were invited to attend the next session early in order to catch up on the missed material. The programme was based on the group programmes previously evaluated, 6,20 but both restitution and compensation strategies were included for all participants. The programme included: one introductory session; three sessions on attention training; three sessions on internal memory strategies; two sessions on external memory aids; and one concluding session to bring together everything that had been learned and to reflect on the best strategies for each individual.…”
Section: Methodsmentioning
confidence: 99%
“…6 The effectiveness of the programme was evaluated with the aim of developing a multicentre randomized trial.…”
Section: Introductionmentioning
confidence: 99%
“…Four of the studies (13,15,18,19) reported that theirs was a manual-based programme, but only two of these manuals (15,18) were accessible. Three of the four studies using a manual (13,15,18) reported how the manual was developed.…”
Section: Programmementioning
confidence: 99%
“…Three of the four studies using a manual (13,15,18) reported how the manual was developed. Although a manual was not used, or not readily accessible, three of the studies (11,12,19) gave session-bysession content, i.e., these three studies gave a clear indication of the topics covered in each group session.…”
Section: Programmementioning
confidence: 99%
“…In rehabilitation, an approach frequently adopted to circumvent these memory problems involves the implementation of appropriate compensatory strategies (Cicerone et al, 2005;das Nair & Lincoln, 2012;Fleming, Shum, Strong, & Lightbody, 2005;Kaschel et al, 2002;Wilson, 1992). For instance, Kaschel et al (2002) demonstrated that mental imagery training improved the memory performance of patients with TBI more than other standard rehabilitation methods (e.g., practical guidelines to improve memory), and that these improvements were accompanied by positive changes in relatives' ratings of patients' memory functioning at the three-month follow-up.…”
mentioning
confidence: 99%